2023
DOI: 10.37680/scaffolding.v5i3.3700
|View full text |Cite
|
Sign up to set email alerts
|

Innovation and Creativity of Islamic Religious Education Teachers in Utilizing Digital-Based Learning Media

Ilma Kharismatunisa

Abstract: This study aims to (1) examine the learning media in teaching Islamic Religious Education, (2) discover the innovation of Islamic Religious Education teachers in utilizing digital-based learning media, (3) unveil the creativity of Islamic Religious Education teachers in developing learning material (4) and imply Religious Education teacher’s innovation and creativity in utilizing digital learning media. The research utilizes a qualitative study with a literature-based approach (Library Research). The research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…With the virtually unlimited nature of digital learning resources, students can access a vast array of learning materials from anywhere, at any time, and with anyone. It opens the opportunity yet a challenge for teachers to continue innovating and being creative in their teaching (Kharismatunisa, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…With the virtually unlimited nature of digital learning resources, students can access a vast array of learning materials from anywhere, at any time, and with anyone. It opens the opportunity yet a challenge for teachers to continue innovating and being creative in their teaching (Kharismatunisa, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in terms of Islamic education, the integration of digital learning media is not only effective but also enriches the relevance of religious education among Muslims. Digital learning media such as internet-connected animated videos, Google Classroom as an online learning platform, Quizziz as an online game, and WhatsApp as a social media application [17] make Islamic education more accessible to a wider audience. This digital learning media can ensure that individuals from various locations can easily engage in religious teachings.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has underscored the integration of innovative and interactive learning methods (Kharismatunisa, 2023;Malik, 2020;Minhaji et al, 2022) in IRE and character-building. These methods focus not just on religious knowledge but also on practical application in daily life.…”
Section: Introductionmentioning
confidence: 99%
“…Aripin & Nurdiansyah (2022) and Jackson (2018) revealed that prior research in this field focused on the traditional transmission of religious knowledge and values, often overlooking life skill development and autonomy aspects. While studies like those conducted by Kharismatunisa (2023) and Malik (2020) have highlighted the importance of innovative and interactive learning methods, this approach has not been fully integrated in the context of IRE and character-building with a focus on autonomy.…”
Section: Introductionmentioning
confidence: 99%